The Kidney Donor Profile Index (KDPI) Correlates With Histopathologic Findings in Post-reperfusion Baseline Biopsies and Predicts Kidney Transplant Outcome - Bachmann, Quirin; Haberfellner, Flora; Büttner-Herold, Maike; Torrez, Carlos; Haller, Bernhard; Assfalg, Volker; Renders, Lutz; Amann, Kerstin; Heemann, Uwe; Schmaderer, Christoph; Kemmner, Stephan (Frontiers in Medicine, 2022)
Background: The increasing organ shortage in kidney transplantation leads to the necessity to use kidneys previously considered unsuitable for transplantation. Numerous studies illustrate the need for a better decision guidance rather than only the classification into kidneys from standard or expanded criteria donors referred to as SCD/ECD-classification. The kidney donor profile index (KDPI) exhibits a score utilizing a much higher number of donor characteristics. Moreover, graft biopsies provide an opportunity to assess organ quality. Methods: In a single center analysis 383 kidney transplantations (277 after deceased and 106 after living donation) performed between January 1st, 2006, and December 31st, 2016, retrospectively underwent SCD/ECD and KDPI scoring. Thereby, the quality of deceased donor kidneys was assessed by using the KDPI and the living donor kidneys by using the living KDPI, in the further analysis merged as (L)KDPI. Baseline biopsies taken 10 minutes after the onset of reperfusion were reviewed for chronic and acute lesions. Survival analyses were performed using Kaplan-Meier analysis and Cox proportional hazards analysis within a 5-year follow-up. Results: The (L)KDPI correlated with glomerulosclerosis (r=0.30, p<0.001), arteriosclerosis (r=0.33, p<0.001), interstitial fibrosis, and tubular atrophy (r=0.28, p<0.001) as well as the extent of acute tubular injury (r=0.20, p<0.001). The C-statistic of the (L)KDPI concerning 5-year death censored graft survival was 0.692. Around 48% of ECD-kidneys were classified as (L)KDPI<85%. In a multivariate Cox proportional hazard analysis including (preformed) panel reactive antibodies, cold ischemia time, (L)KDPI, and SCD/ECD-classification, the (L)KDPI was significantly associated with risk of graft loss (hazard ratio per 10% increase in (L)KDPI: 1.185, 95% confidence interval: 1.033-1.360, p=0.025). Survival analysis revealed decreased death censored (p<0.001) and non-death censored (p<0.001) graft survival in kidneys with an increasing (L)KDPI divided into groups of <35%, 35-85%, and >85%, respectively. Conclusion: With a higher granularity compared to the SCD/ECD-classification the (L)KDPI is a promising tool to judge graft quality. The correlation with chronic and acute histological lesions in post-reperfusion kidney biopsies underlines the descriptive value of the (L)KDPI. However, its prognostic value is limited and underlines the urgent need for a more precise prognostic tool adopted to European kidney transplant conditions.